Comparison of Pyroxasulfone, S‐metolachlor, and Mesotrione for Weed Control in Sweet Corn on Organic Soils. Issue 1 (27th February 2013) - Odero, Dennis C.; Wright, Alan L.
Abstract : Field experiments were conducted at the Everglades Research and Education Center in Belle Glade, FL, during 2011 and 2012 to evaluate weed control and sweet corn response to preemergence application of pyroxasulfone, S ‐metolachlor, and mesotrione on high organic matter soils (up to 85%) of the Everglades Agricultural Area (EAA) in southern Florida. Pyroxasulfone (0.21 and 0.43 lb a.i./acre) controlled spiny amaranth, common lambsquarters, and common purslane 91 to 100, 95 to 100, and 94 to 99% at 49 days after treatment (DAT), respectively. S ‐metolachlor (2.48 and 4.97 lb a.i./acre) controlled these respective weeds 98 to 99, 17 to 42, and 70 to 80%. Mesotrione (0.19 lb a.i./acre) at this timing controlled spiny amaranth, common lambsquarters, and common purslane 78, 95, and 24%, respectively. No above ground visible injury of sweet corn was observed irrespective of herbicide or rate. Overall, pyroxasulfone resulted in higher sweet corn yield compared to S ‐metolachlor and mesotrione. The results of this study show that preemergence pyroxasulfone can provide effective residual control of problematic broadleaf weeds that is more consistent than S ‐metolachlor or mesotrione in sweet corn on high organic matter soils of the EAA.